Household member arrest and adolescent externalizing behaviors: The roles of family and peer climates. (October 2021) - Copp, Jennifer E.; Johnson, Elizabeth I.; Bolland, Anneliese C.; Bolland, John
Highlights: Household member incarceration influenced youths' behavioral and criminal justice outcomes. Youths' social climates and emotion regulation emerged as important mechanisms. Yet these factors explained a small portion of the effect of household member incarceration. Findings stress the need for additional research on the cj involvement of youths' broader networks. Future research should focus in particular on the ways in which such involvement confers risk. Abstract: Although research on the intergenerational consequences of criminal justice contact has focused primarily on parental incarceration, scholars have called for greater attention to the reverberating effects of other family members' entanglements with law enforcement on youth. Using longitudinal data from the Mobile Youth Survey (MYS), this study examines direct and indirect linkages between household member arrest and youth outcomes and considers the roles of social (parenting, peer normative climate) and emotional (anger expression) processes. Results suggest that household members' involvement with the criminal justice system has consequences for youth's behavioral and criminal justice outcomes. Moreover, although social and emotional processes appeared to "matter, " they did not account for the negative outcomes associated with household member arrest. Results suggest the importance of adopting broader perspectives on family criminal justice contact that include attention to household member arrest as well as to both direct and indirect effects. Findings are discussed in terms of directions for future research and the need to specify mechanisms by which household member arrest may increase risk for adverse youth outcomes.